CLIMATE CHANGE ADAPTATION AND MITIGATION STRATEGIES IN THE CONTEXT OF IMPROVING PUBLIC HEALTH: A SYSTEMATIC LITERATURE REVIEW - Erian Fatria; Eka Apriyanti; Agus Priadi (Universitas Sebelas Maret (UNS), 2026)
Climate change represents a critical global health threat, necessitating effective adaptation and mitigation strategies. While numerous studies have examined climate strategies in specific regions, a comprehensive analysis comparing approaches across multiple continents and identifying the most effective strategies from a global public health perspective remains limited. This systematic literature review followed PRISMA guidelines, analyzing 21 studies from 2014-2024 sourced from ScienceDirect, Google Scholar, PubMed, and EBSCOhost. The review included studies examining climate adaptation and mitigation strategies with measurable public health outcomes across diverse geographical contexts. The analysis identified five key strategy categories. Health system strengthening and leadership emerged as the most frequently implemented approach (12 countries), demonstrating effectiveness through improved emergency response coordination and resource allocation. Environmental conservation strategies (8 countries) showed significant benefits in reducing direct climate impacts, while green economy approaches (8 countries) provided sustainable funding mechanisms. The findings reveal that contextual implementation varies significantly between developed and developing nations. Effective climate-health action requires tailored approaches that consider local capacities and resources. Leadership and health system strengthening provide the foundational framework for successful implementation, while integrated multi-sectoral approaches deliver the most comprehensive public health protection. Future policies should prioritize context-specific strategies that address both immediate health risks and underlying climate drivers.